Three new species of Cladosporium from Madhya Pradesh, India - S.A. FIRDOUSI, A.N. RAI; K.M. VYAS, C.D. SHARMA, K.K. GADPANDEY (Indian Phytopathology, 2002)
Three new species of Cladosporium viz. C. glochidionis, C. malvacearum and C. kapildharens are described, illustrated and compared with closely related species. These cause leaf spot disease on various Angiospermic flora.